Explaining the sawtooth: latitudinal periodicity in a circadian gene correlates with shifts in generation number. (27th December 2014) - Levy, R. C.; Kozak, G. M.; Wadsworth, C. B.; Coates, B. S.; Dopman, E. B.
Abstract Many temperate insects take advantage of longer growing seasons at lower latitudes by increasing their generation number or voltinism. In some insects, development time abruptly decreases when additional generations are fit into the season. Consequently, latitudinal 'sawtooth' clines associated with shifts in voltinism are seen for phenotypes correlated with development time, like body size. However, latitudinal variation in voltinism has not been linked to genetic variation at specific loci. Here, we show a pattern in allele frequency among voltinism ecotypes of the European corn borer moth (Ostrinia nubilalis) that is reminiscent of a sawtooth cline. We characterized 145 autosomal and sex‐linked SNPs and found that period, a circadian gene that is genetically linked to a major QTL determining variation in post‐diapause development time, shows cyclical variation between voltinism ecotypes. Allele frequencies at an unlinked circadian clock gene cryptochrome1 were correlated with period. These results suggest that selection on development time to 'fit' complete life cycles into a latitudinally varying growing season produces oscillations in alleles associated with voltinism, primarily through changes at loci underlying the duration of transitions between diapause and other life history phases. Correlations among clock loci suggest possible coupling between the circadian clock and the circannual rhythms for synchronizing seasonal life history. We anticipate that latitudinal oscillations in allele frequency will represent signatures of adaptation to seasonal environments in other insects and may be critical to understanding the ecological and evolutionary consequences of variable environments, including response to global climate change.